Variable interstellar radiation fields in simulated dwarf galaxies: supernovae versus photoelectric heating - Hu, Chia-Yu; Glover, Simon (Monthly notices of the Royal Astronomical Society, 2017)
Abstract: We present high-resolution hydrodynamical simulations of isolated dwarf galaxies including self-gravity, non-equilibrium cooling and chemistry, interstellar radiation fields (ISRF) and shielding, star formation, and stellar feedback. This includes spatially and temporally varying photoelectric (PE) heating, photoionization, resolved supernova (SN) blast waves and metal enrichment. A new flexible method to sample the stellar initial mass function allows us to follow the contribution to the ISRF, the metal output and the SN delay times of individual massive stars. We find that SNe play the dominant role in regulating the global star formation rate, shaping the multiphase interstellar medium (ISM) and driving galactic outflows. Outflow rates (with mass-loading factors of a few) and hot gas fractions of the ISM increase with the number of SNe exploding in low-density environments where radiative energy losses are low. While PE heating alone can suppress star formation as efficiently as SNe alone can do, it is unable to drive outflows and reproduce the multiphase ISM that emerges naturally whenever SNe are included. We discuss the potential origins for the discrepancy between our results and another recent study that claimed that PE heating dominates over SNe. In the absence of SNe and photoionization (mechanisms to disperse dense clouds), the impact of PE heating is highly overestimated owing to the (unrealistic) proximity of dense gas to the radiation sources. This leads to a substantial boost of the infrared continuum emission from the UV-irradiated dust and a far-infrared line-to-continuum ratio too low compared to observations.